Antimicrobial resistance of Staphylococcus aureus among cooked food and food handlers associated with their occupational information in Klang Valley, Malaysia - Seow, Wen Li; Mahyudin, Nor Ainy; Amin Nordin, Syafinaz; Radu, Son; Abdul Mutalib, Noor Azira (Elsevier, 2021)
The purpose of the study was to identify the prevalence of Staphylococcus aureus and its antimicrobial resistance profile among food handlers and in cooked food in Klang Valley, Malaysia. The correlation between the prevalence of S. aureus and the occupational information of the food handlers was also identified. Two hundred hand swab samples and 100 cooked food samples were collected from Grade A, B, and C food premises, whereby the occupational information of food handlers was also recorded. The results showed that the prevalence of S. aureus among food handlers and in cooked food was 95.0% and 50.0%, respectively. None of the methicillin-resistant S. aureus (MRSA) strains had been isolated from the food handlers, whereas four (8.0%) cooked food samples were detected with the MRSA strains. Antibiotic susceptibility tests showed that 57.9%, 13.7%, 3.2% and 1.1% of the isolates from food handlers’ hands were resistant to penicillin-G, erythromycin, clindamycin and mupirocin, respectively. In addition, isolates from food samples showed that 58.0%, 8.0%, 8.0% and 18.0% were resistant to penicillin-G, cefoxitin, erythromycin, and clindamycin, respectively. All of the isolates from cooked food had shown susceptible to mupirocin. Multidrug-resistance S. aureus strains were isolated from two non-Malaysian food handlers and two cooked food samples. Furthermore, grading system (P = 0.000), grade of food premises (P = 0.010), working responsibility (P = 0.026), and year of employment (P = 0.049) of food handlers were significantly correlated with the prevalence of S. aureus. Nonetheless, no correlation was found between multidrug-resistant S. aureus with the occupational information of food handlers. This urges for improvements in constructive and sustainable food safety practises among food handlers to reduce the risk of foodborne illness outbreaks.